Aplicación de contabilidad comercial en “Pandub original”, ubicado en el cantón Lago Agrio, provincia de Sucumbíos, periodo: mayo – junio 2016 - Suárez Agila, Matilde Beatriz (2017)
Accounting is essential in all organizations that perform acts of commerce, its functions allow to know and maintain control of the economic and financial situation, besides the operational area of the business at any time as in the case of PANDUB ORIGINAL shoe store. Through the application of the accounting process, it was complied with what was proposed at the beginning of the investigation, applying the accounting system for the permanent inventory period May-June 2016; To control and determine the cost of goods, in addition to the application of IAS 16, which allows determining the depreciation of goods as determined by the Organic Law of the Internal Tax Regime, article 28 numeral 6; Values that influence the expenses. The objectives were met, the methodology used consisted of the collection, collection and registration of securities, assets, rights and obligations according to the supporting documents and physical verification; The journal was processed, internal documents and balance sheets were prepared. Completed the process predominates the importance of accounting principles and treatment group accounts of property, Plant and Equipment based on the accounting Standard IAS 16 which allow to obtain reasonable Financial Statements for proper decision making.